Teaching children with autism to respond to conversation partners' interest. Issue 3 (6th August 2015) - Peters, Lindsay C.; Thompson, Rachel H.
<x xml:space="preserve">Abstract</x> Successful conversation requires that the speaker's behavior is sensitive to nonvocal listener responses. We observed children with autism spectrum disorder during conversation probes in which a listener periodically displayed nonvocal cues that she was uninterested in the conversation. We used behavioral skills training to teach conversation skills. First, we taught participants to tact nonvocal listener behavior (interested or uninterested), but this was insufficient to improve responding aimed at regaining listener interest. Participants were then taught to ask a question (Experiments 1 and 2) or change the topic (Experiment 2) when the listener was uninterested. Responding persisted over time and with changes in the stimulus conditions. The behavior change was also deemed socially valid by blind observers. In Experiment 3, participants learned to shift to the other trained response when exposed to extinction. This study illustrates a set of procedures for bringing speaker behavior under control of nonvocal listener cues.